1996
DOI: 10.1016/s0014-5793(96)01286-0
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids of the α1B‐adrenergic receptor involved in agonist binding: differences in docking catecholamines to receptor subtypes

Abstract: Site-directed mutagenesis and molecular dynamics analysis of the 3-D model of the ale-adrenergic receptor (AR) were combined to identify the molecular determinants of the receptor involved in catecholamine binding. Our results indicate that the three conserved serines in the fifth transmembrane domain (TMD) of the ale-AR play a distinct role in catecholamine binding versus receptor activation. In addition to the amino acids D125 in TMDIII and S207 in TMDV directly involved in ligand binding, our findings ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
67
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 13 publications
5
67
1
Order By: Relevance
“…Furthermore, Asp125 of the a 1B -AR is the homologous to the aspartate on TMDIII of b 2 -and a 2A -AR and Dopamin1-receptor (D 1 -R) involved in the interaction with the amino group of catecholamines. 16) In the present study, mutation of Asp125 to alanine totally impaired the ability of the a 1b -AR to bind both agonists and antagonists. Although prazosin is a non-selective drug for a 1b -AR and after mutation we could not determine any detectable data for mutant Asp125Ala.…”
Section: Discussionsupporting
confidence: 43%
“…Furthermore, Asp125 of the a 1B -AR is the homologous to the aspartate on TMDIII of b 2 -and a 2A -AR and Dopamin1-receptor (D 1 -R) involved in the interaction with the amino group of catecholamines. 16) In the present study, mutation of Asp125 to alanine totally impaired the ability of the a 1b -AR to bind both agonists and antagonists. Although prazosin is a non-selective drug for a 1b -AR and after mutation we could not determine any detectable data for mutant Asp125Ala.…”
Section: Discussionsupporting
confidence: 43%
“…1), and this residue has been shown to play a role in ligand binding and receptor activation in the ␣ 1A , ␣ 2A , and ␣ 1B adrenergic (5)(6)(7)(8) and the dopamine D 1 , D 2 , and D 3 receptors (9 -13). In the rat ␣ 1A AR, in which a Ser is absent at 5.43, Ser-188 5.42 (aligned with ␤ 2 AR Ser-203 5.42 ) interacts with the mOH of catecholamines, and it is this H bond that is critical for ligand binding and receptor activation (5).…”
mentioning
confidence: 99%
“…Furthermore, Asp125 of the a 1b -AR is the homologous to the aspartate on TMD III of b 2 -and a 2A -AR and dopamine1-receptor involved in the interaction with the amino group of catecholamines. 25) Cavalli and co-workers reported that mutation of Asp125 to alanine totally impaired the ability of the a 1b -AR to bind both agonists and antagonists. This was shown by the fact that Asp125Ala displayed no specific [ 125 I]HEAT binding and no epinephrine-induced stimulation of IP production.…”
Section: Discussionmentioning
confidence: 99%